Aggressive aneurysmal bone cyst in association with polyostotic fibrous dysplasia: A case report. (2015) - Anderson, Nathan; DiBella, Claudia; Pianta, Marcus; Slavin, John; Choong, Peter
Highlights: Aneurysmal bone cyst occurring in the setting of previously diagnosed fibrous dysplasia is a rare occurrence. Repeat investigation with imaging and biopsy was required to obtain accurate diagnosis and exclude malignancy. Due to the aggressive nature of the disease and the patient's medical comorbidities, an above knee amputation was required for disease control. Abstract: Introduction: Aneurysmal bone cyst occurring in the setting of previously diagnosed fibrous dysplasia is rare. While both are benign processes, pain, compression of nearby structures and risk of fracture can require treatment. Presentation of case: In this report, we describe a 56 year old male who developed an aggressive aneurysmal bone cyst secondary to fibrous dysplasia in the proximal tibia over a period of 8 months. He required an above knee amputation for disease and symptom control due to the aggressive nature of disease and medical comorbidities. Discussion: The diagnosis of a secondary lesion can prove difficult. It is important to exclude a malignant disease process, particularly when imaging demonstrates an aggressive appearance. In this case, repeat imaging, CT guided biopsies and an open biopsy were performed to exclude malignancy prior to definitive surgical management. Conclusion: In order to exclude secondary lesions, we suggest further investigation for new onset pain in the setting of a benign lesion.